Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Kesucian Hidup Mahasiswa Menurut Perspektif Kekristenan - Gabriel A. P. Saragih; Fernando A. M. Saragih (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
Holiness of life is a pattern of life based on the truth of God's Word, which is very important for students to apply in their daily lives. However, the sanctity of life is increasingly rare due to various factors. This study aims to analyze the factors that influence the level of sanctity of life in college students. The method used is qualitative, with data collection through searching and selecting relevant articles from scientific sources. The results show that there are two types of factors that affect the sanctity of life: general factors that are often experienced by university students, and specific factors that originate from within Christianity. Students need to be vigilant, selective, and strive to maintain the sanctity of life in the midst of various challenges.